Contemporary outcomes of pancreaticoduodenectomy for benign and precancerous cystic lesions. Issue 9 (September 2022) - Aizpuru, Matthew; Starlinger, Patrick; Nagorney, David M.; Smoot, Rory L.; Truty, Mark J.; Kendrick, Michael L.; Cleary, Sean P.
Abstract: Background: The decision to undertake pancreaticoduodenectomy for benign and precancerous lesions has historically relied on outcomes data from operations for cancer. We aimed to describe risks for these specific patients and identify the highest risk groups. Methods: The ACS-NSQIP pancreatic targeted data was queried for pancreaticoduodenectomies for benign and pre-cancerous neoplasms from 2014 to 2018. Baseline characteristics, operative techniques and outcomes were examined. Multivariate regression was performed to identify predictors of major complications. Results: 748 patients underwent pancreaticoduodenectomy for (n = 541, 72.3%) IPMN, (n = 87, 11.6%) MCN, (n = 78, 10.4%) serous cystadenoma, and (n = 42, 5.6%) solid pseudopapillary neoplasm. Median LOS was 8 days. Major complications (n = 135, 18.0%), non-home discharges (n = 83, 11.1%) and readmissions (n = 153, 20.5%) occurred frequently. In patients ≥ 80 years of age (n = 37), major complications (n = 11, 29.7%) and non-home discharge (n = 9, 24.3%) were quite common. 5-item modified frailty index ≥ 0.4 (OR 1.84, 95%CI 1.06–3.19, p = 0.030), Male sex (OR 1.729, 95%CI 1.152–2.595, p = 0.008), Age ≥ 65 (OR 1.63, 95%CI 1.05–2.54, p = 0.29) and African-American race (OR 2.50, 95%CI 1.22–5.16, p = 0.013) were independent predictors of major morbidity. Conclusions: Pancreaticoduodenectomies in this setting have high rates of major complications. Morbidity extends beyond the index hospitalization, with frequent readmission and non-home discharge. Patient specific factors, rather than technical or disease factors predicted outcomes. In certain patients, particularly those older than 80, the morbidity of this operation may exceed the cancer prevention benefits.